High porous ceramics with isometric pores by a novel saponification/gelation/freeze-casting combined route. Issue 14 (November 2021) - Santos, Larrisea Nathiere Rangel de Morais; Cartaxo, Juliana de Melo; Silva, José Rodrigo Sousa; Rodrigues, Alisson Mendes; Dantas, Eugênia Livia de Andrade; de Sousa, Frederico Barbosa; Neves, Gelmires de Araújo; Menezes, Romualdo Rodrigues
Highlights: High porous bodies were produced by a novel saponification/gelation/freeze-casting combined route. Use of in situ saponification led to the production of pore cells large than 100 μm. Isometric pores were achieved with the saponification/gelation combined route, despite the use of water as solvent. Abstract: A new route based on the combination of saponification/gelation/freeze-casting processes, in which the water was used as the solvent, was proposed to produce highly porous ceramics with isometric pores. The saponification reaction using gelatin promoted an inter-connected and equiaxial pore structure with the absence of lamellar pores, even using water as a solvent. The final porosity was up to ∼95 %, and the average pore size ranged from ≈200 up to 500 μm. The amount of saponifying agent had a significant influence on the pore size, while the contents of solids had a more substantial effect on the open porosity. The results indicate that the in situ production of surfactant combined with freeze casting technique allows obtaining ceramics with high porosity and isometric pores even using water as a solvent.